Secular trends in antidepressant prescribing in the UK, 1975–1998 - Middleton, Nicos; Gunnell, David; Whitley, Elise; Dorling, Daniel; Frankel, Stephen (My University, 2001)
Background we have examined secular trends in age‐ and sex‐specific prescribing of antidepressants to determine whether these mirror changes in other population measures of mental health.Method an analysis was carried out of age‐ and sex‐specific rates of antidepressant prescribing by a representative sample or panel of UK general practitioners (GPs) in the period 1975–1998.Results the number of antidepressant prescriptions issued increased more than twofold in the period 1975–1998 and, in 1998, a total of 23.4 million antidepressant prescriptions were issued by GPs in the United Kingdom. Rates of antidepressant prescribing increased markedly in all age and sex groups with as much as a threefold increase in the older age groups. With the exception of 12–19‐year‐olds, these increases have been more marked in males, although absolute levels of prescribing are still at least two times higher in females.Conclusions antidepressant prescribing has increased in all age and sex groups. This indicates either that there have been changes in the presentation, recognition and management of depression in general practice or that the prevalence of depression has increased, or a combination of these two phenomena. The higher prescribing rate in females is in keeping with evidence from psychiatric morbidity surveys suggesting that women experience higher levels of psychiatric morbidity than men. Decreases in the ratio of female to male prescribing, however, support other data indicating that, relative to females, the mental health of young males has declined in recent years. Changes in patterns of help‐seeking may also contribute to the observed trends.
Keywords: Antidepressant prescribing; Mental health; Suicide